Sinapic Acid Regulates Glucose Homeostasis by Modulating the Activities of Carbohydrate Metabolizing Enzymes in High Fat Diet Fed-Low Dose STZ Induced Experimental Type 2 Diabetes in Rats - Ramesh Nithya; Vellai Roshana Devi; Rajendran Selvam; Sorimuthu Pillai Subramanian (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2017)
Diabetes Mellitus is a chronic metabolic disorder arises due to absolute lack of insulin secretion (T1DM) or its action or both (T2DM). Alterations in glucose metabolism in DM are frequently accompanied by impairment in the activities of enzymes that regulate carbohydrate metabolism. Liver is a vital organ that acts as primary site of endogenous glucose production through gluconeogenesis or glycogenolysis. The enzymes that control glucose metabolism in the liver tissue are considered as potential targets for the maintenance of normal glycemic control in diabetic individuals. Search for new drugs with more efficacies and without side effects preferably from plant origin continues. Sinapic acid is one such phytochemical which lacks scientific validation for its folklore use. It is a naturally occurring carboxylic acid belongs to phenylpropanoid family. It is widely distributed in the various sources such as rye, mustard, berries and vegetables In the present study it was aimed to systematically study the efficacy of sinapic acid (25mg/kg.b.w./rat for 30 days) in the regulation of glucose homeostasis modulating the activities of carbohydrate metabolizing enzymes in hepatic tissues of high fat diet fed-low dose STZ induced experimental type 2 diabetes in rats. The altered activities of carbohydrate metabolizing enzymes such as glucokinase, pyruvate kinase, glucose-6-phosphatase, fructose-1,6-bisphosphatase, glucose-6-phosphate dehydrogenase, lactate dehydrogenase in hepatic tissues of diabetic rats were significantly reverted to near normalcy upon oral treatment with sinapic acid. In addition, oral administration of sinapic acid to experimental diabetic groups of rats showed significant reduction in the levels of fasting blood glucose and glycosylated hemoglobin and increased level of plasma insulin and hemoglobin. Thus, the present data demonstrated that the oral administration of sinapic acid to diabetic rats regulates glucose homeostasis by regulating the activities of carbohydrate metabolizing enzymes.